Exploring Residential Rooftop Solar Potential in the United States by Race and Ethnicity - Reames, Tony G. (Frontiers in Sustainable Cities, 2021)
Over the last decade, the United States has experienced continued growth in residential rooftop solar photovoltaic (PV) adoption. However, solar adoption disparities have been shown across household income, homeownership status, and more recently racial and ethnic demographics. A key component to ensuring a just clean energy transition is understanding the existing landscape to establish realistic goals. Motivated by studies on solar adoption disparities, this descriptive study aims to evaluate the distribution of estimated single-family rooftop potential across racial and ethnic majority census tracts to discern whether rooftop potential disparities may justify solar adoption disparities. Across all census tracts, the median rooftop potential was 80%. Three-fourths of all census tracts had a rooftop potential greater than 72%, regardless of racial/ethnic majority. Compared to majority-white census tracts, majority-Black, majority-Hispanic, and majority-Asian census tracts had slightly lower rooftop potential, 6%, 7%, and 9%, respectively, while majority-American Indian census tracts had an 11% higher rooftop potential. The slightly lower rooftop potential in communities of color compared to majority-white and non-racial/ethnic majority census tracts, alone, was not of the magnitude to justify documented racial/ethnic disparities in solar adoption. This study concludes, that while a majority of homes in communities of color are solar suitable, an equitable clean energy transition is only possible with policies, programs, and incentives that center on racial equity while recognizing the interplay between race, income, and homeownership status.